Advancing the Competitiveness of MSMEs Through Local Government Policy Strategies in the Ijen Geopark, Indonesia - Suji, Suji; Suryawati, Dina; Helpiastuti, Selfi Budi; Supranoto, Supranoto; Molasy, Honest Dody; Firdaus, Alfareza (Journal of Governance and Public Policy, 2026)
Despite growing recognition of UNESCO Global Geoparks as instruments of local economic development, existing studies largely focus on geotourism potential or aggregate economic impact, leaving a gap in comparative, policy-focused analyses that explain why benefits are unevenly distributed within a single geopark area. This study examines public policy strategies to improve MSME competitiveness in the Ijen UNESCO Global Geopark through a comparative analysis of Bondowoso and Banyuwangi Regencies in East Java, Indonesia. Although both share the same geopark designation, Banyuwangi demonstrates stronger MSME integration and tourism branding, while Bondowoso faces persistent structural governance challenges. Drawing on Dunn's (2018) integrated public policy analysis framework, this study applies formal problem structuring and policy recommendation through the non-dominated alternatives method. Data were collected through semi-structured interviews, focus group discussions, observation, and document analysis involving MSME actors and key government stakeholders. Findings revealed that the performance gap is driven primarily by institutional design differences, specifically the absence of a lead agency and ad hoc inter-agency coordination in Bondowoso, rather than budget disparities. Evaluating twelve policy alternatives across three feasibility criteria, this study recommends One-Stop Integrated Services for MSMEs as the priority strategy, functioning as a governance hub that enables complementary interventions to operate in an integrated manner. Empirically, this study provides the first comparative evidence that geopark status alone does not determine MSME competitiveness. Conceptually, it operationalizes the policy-economy mismatch thesis in the Indonesian geopark context. Methodologically, it advances the field by producing evidence-based, ranked policy recommendations replicable in other geopark settings.